Hallmarks of primary headache: part 2– Tension-type headache - Li-Ling Hope Pan; Yu-Hsiang Ling; Shuu-Jiun Wang; Linda Al-Hassany; Wei-Ta Chen; Chia-Chun Chiang; Soo-Jin Cho; Min Kyung Chu; Gianluca Coppola; Adriana Della Pietra; Zhao Dong; Esme Ekizoglu; et al. (The Journal of Headache and Pain)
Abstract Background and aim Tension-type headache is the most prevalent primary headache disorder. While the episodic subtype is more common, chronic tension-type headache significantly impacts health-related quality of life and contribute to increased healthcare utilization and disability. Despite considerable advances in the understanding of tension-type headache, critical gaps persist. This paper aims to provide a comprehensive review of the hallmarks of tension-type headache, from its pathophysiology, comorbidities, treatment options, to psychosocial impact. Main results Multiple factors are associated with tension-type headache, including peripheral mechanisms (increased muscle tenderness and myofascial trigger points), central sensitization, genetic predisposition, and psychological comorbidities such as anxiety and depression. Neuroimaging and neurophysiological studies demonstrated altered pain processing in cortical and subcortical regions in patients with tension-type headache. Regarding treatment strategy, in addition to pharmacological treatment, novel insights into non-pharmacological interventions such as cognitive behavioral therapy, neuromodulation techniques, physical therapy, mindfulness, lifestyle management, and patient education were highlighted as valuable components of comprehensive management strategies. Conclusions A complex interplay between peripheral and central mechanisms and psychosocial stressors underpins tension-type headache. Integrated multidisciplinary approaches combining pharmacological and non-pharmacological interventions are critical for optimal patient outcomes. Further research should continue to refine the understanding of these mechanisms to improve targeted therapeutic strategies and reduce the global burden of tension-type headache.